Towards Multitarget Testing in Molecular Microbiology - Deborah Steensels; Anne Vankeerberghen; Hans De Beenhouwer (International Journal of Microbiology)
Advantages of PCR assays over more conventional culture-based diagnostics include significantly higher sensitivities and shorter turnaround times. They are particularly useful when patient treatment has already been initiated or for specimens that may contain microorganisms that are slow-growing, difficult to culture, or for which culture methods do not exist. However, due to genome variability, single target testing might lead to false-negative results. This paper focuses on examples from our own experiences and the literature to provide insight into the limitations of single target testing in molecular biology. Lessons learned from these experiences include the careful design of diagnostic assays, preferably multitargeted, the importance of investigating the incidence and epidemiology of infection in detail, the frequent participation in appropriate quality assurance schemes, and the importance of continuous attentiveness by investigators when confronted with inconsistent results. In conclusion, multitargeted testing in microbiological molecular assays should be a rule.